Analisis Efektivitas Mesin Batching Plant 1 dan Mesin Batching Plant 2 dengan Overall Equipment Effectiveness Pada PT. X - Nia Budi Puspitasari; Eldinda Sazida Permatasari (Performa: Media Ilmiah Teknik Industri, 2015)
Overall Equipment Effectiveness (OEE) is one of Total Productive Maintenance (TPM) application program, which aims to determine the effectiveness of a machine. PT. X has 3 machine batching plant where machine 1 and 2 used effectively, from the data historically known that the machines batching plant 1 having a value greater namely 1030 minutes compared to the engine batching plant 2 that have value 240 minutes. This research measures the OEE value of two machines Bactching Plant and then compares the results. The value obtained is 82.71% for machine 1 and 84.83% for machine 2. This research suggests that the performance factor is the biggest problem in the machine OEE values, because the enterprise systems is make to order, the recommended action is to maximize the production capacity of each machine by considering a more accurate production targets in each period.